Outcomes and technical aspects of liver retransplantation with living donors in children. (21st June 2016) - Feier, Flavia; da Fonseca, Eduardo A.; Candido, Helry L.; Pugliese, Renata; Benavides, Marcel R.; Neiva, Romerito; Chapchap, Paulo; Seda‐Neto, Joao
Abstract: Re‐LT is the only recourse for patients with liver graft failure. However, survival rates after re‐LT are lower than those of primary transplants. Few reports are available regarding re‐LT with LDs in children. The objective of this study was to describe our cohort of patients retransplanted with LD and emphasize the technical aspects of a re‐LT with LD. This is a retrospective report of a series of 18 children (<18 yr old) submitted to 20 re‐LT from January 1997 to December 2013 at Hospital Sirio‐Libanes and Hospital AC Camargo Cancer Center. The one‐ and five‐yr survival for patients retransplanted with LD was 70.6% and 58.6%. Little technical modifications from a regular LD primary transplant were needed in patients retransplanted with LD. Seven (38.8%) patients presented vascular complications following re‐LT and three presented biliary complications (16.6%). In conclusion, a re‐LT with LD is an acceptable alternative for children who experience liver graft failure and it does not compromise the donor pool. Further experience with re‐LT with LD may support this therapy.